Pengaruh Media Pembelajaran Virtual Reality Box (Vr Box) terhadap Motivasi, Minat, dan Disiplin Belajar Praktik Pengelasan pada Siswa SMK - Rezeki Genesis Sitompul; Waskito Waskito (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
This study aims to determine the effect of Virtual Reality Box (VR BOX) as a learning medium on students' motivation, interest, and learning discipline in welding practice for grade XI students of the Machining Engineering Department at SMK Negeri 1 Tanjung Raya. The research method used is quantitative with a quasi-experimental design applying the non-equivalent control group design approach. Data were collected through tests and observation and analyzed using validity tests, reliability, normality, homogeneity, t-tests, ANOVA, and coefficient of determination. The results showed that the use of VR BOX significantly influenced students' motivation, interest, and learning discipline. The implementation of VR media created interactive learning, increased student engagement, and reduced fear in welding practice. It can be concluded that VR BOX is an effective instructional medium to improve the quality of vocational practice learning in vocational schools.